Labour law and non-standard employment: case studies of selected workplaces in Makhanda - Mini, Sifanelwa (Rhodes University, Faculty of Humanities, Department of Sociology)
While precarious and poorly-regulated forms of employment are on the increase worldwide, the patterns vary significantly over time and space. This study sought to understand employees' perceptions of non-standard employment (NSE), the reasons why employers resort to NSE and why they use particular types of NSE. In addition, the research explored how labour law protections for NSE are applied in particular workplaces. Drawing on the regulation approach, which provides a conceptual framework to explain changes in production and employment relationships under specific spatio-temporal conditions, this study focused on three companies in Makhanda. Furthermore, this study employed a qualitative research method to explore the employees' perceptions on non-standard work. This was done by using an interpretive approach to explore how workers experience NSE and how Eastern Cape citizens in Makhanda navigate the scourge of unemployment and exploitation in the labour market. Moreover, the research investigated how employees experience the efficacy of their employment rights in the workplace. The employment rights observed in the study include (among others) leave, contract of employment and collective bargaining; all of which are provisions in the Labour Relations Act. The findings in the study do validate the use of NSE as a 'tool' to curb high unemployment. However, the study finds that the positive result of job creation does not signify job security for non-standard workers, instead beneath the rhetoric of job creation and investment, lies hidden the exploitation of vulnerable groups of citizens and extension of precarious forms of employment. This is because businesses engage in economic competition locally and globally. Therefore, in order to successfully compete against other, employer's cut on labour expenses by adopting a "race to the bottom," the effect of which is paying employees below the minimum wage. Moreover, this study opposes the argument that NSE is a stepping stone to permanent employment. The conditions which prevail in NSE are distinctly different from those in the Standard Employment Relationship (SER), making it difficult for employees to transition to a new labour market. The latter is more aligned with the heterodox approach than it is to the orthodox approach to labour market.
Keywords: Non-standard employment -- South Africa -- Makhanda; Job security; Labor market -- South Africa; Labor laws and legislation -- South Africa; Work-life balance -- South Africa; Temporary employment -- South Africa; Collective bargaining -- South Africa